+0  
 
0
235
1
avatar

Algebra 2 help: functions

Guest Oct 12, 2017
 #1
avatar+87556 
+2

 

Leading coefficient 2, zeroes   =  2, √2, -√2

 

So...we can write this as

 

2 ( x - 2) (x - √2) (x + √2)  =

2(x - 2) (x^2  - 2)  =

2 (x^3 - 2x^2 - 2x + 4)  =

2x^3 - 4x^2 - 4x + 8

 

Similarly....we have

 

Leading coefficient -1, zeroes   =  1, 1 +√3,  1-√3

 

-1 ( x -1) ( x - [1 +√3] ) ( x  - [ 1 -√3] )  =

-1 (x - 1) ( x^2  - [ 1 + √3]x  - [ 1 -√3] x  +  [1 +√3] [1 -√3] )  =

-1 (x - 1) (x^2 - x - √3x  - x + √3x  + 1  - 3 )  =

-1 (x - 1)  (x^2 - 2x -2)  =

-1( x^3 -x^2 - 2x^2 + 2x - 2x + 2) =

-1 (x^3 - 3x^2 + 2) =

-x^3 + 3x^2 - 2

 

 

cool cool cool

CPhill  Oct 12, 2017

10 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.